Impacts of Thermal Activation on Physical Properties of Coal Gangue: Integration of Microstructural and Leaching Data - Wangtao Fan; Yuan Chen; Runxia Zhang; Xiaoguang Chen; Jin Li; Zhaolin Gu; Jianyun Wang (Buildings)
The recycling of coal gangue has considerable potential to produce secondary environmental hazards, which significantly influence the high-end application of coal gangue in practical engineering. The present study investigates the effects of activation treatment on the physical, chemical properties and leaching behavior of coal gangue. The mineral composition, micro-pore structure and element leaching were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Thermogravimetry Analysis (TG), Low-Temperature Nitrogen Adsorption (LTNA) and Inductively Coupled Plasma (ICP). The results indicate that kaolinite and pyrite in coal gangue experienced reconstruction after 600 °C during thermal activation. The density of thermally activated coal gangue is increased with the calcination temperature as well as the alkalinity (from 4.8–7.1) due to the burning of organic and the oxidation of pyrite. The calcination treatment induced the reduction in macropore volume (>50 nm), and enhancement in mesopore (<5 nm) volume. Leachable Ni, Cd, Mn, Cu, Zn and Pd decreased by 99%, 67%, 86%, 40%, 99% and 93% after calcination at 800 °C, respectively. The Si and Al in 800 °C calcined coal gangue exhibited a high leaching ability in alkalinity solution; leachable Al reached 106.4 mg/kg, while leachable Si reached 86.1 mg/kg after 48 h of dynamic leaching.